Sun-mediated Mechanical LINC between Nucleus and Cytoskeleton Regulates βcatenin Nuclear Access - Uzer, Gunes (J Biomech, 2018)
βcatenin acts as a primary intracellular signal transducer for mechanical and Wnt signaling pathways to control cell function and fate. Regulation of βcatenin in the cytoplasm has been well studied but βcatenin nuclear trafficking and function remains unclear. In a previous study we showed that, in mesenchymal stem cells (MSC), mechanical blockade of adipogenesis relied on inhibition of βcatenin destruction complex element GSK3β (glycogen synthase kinase 3β) to increase nuclear βcatenin as well as the function of Linker of Cytoskeleton and Nucleoskeleton (LINC) complexes, suggesting that these two mechanisms may be linked. Here we show that shortly after inactivation of GSK3β due to either low intensity vibration (LIV), substrate strain or pharmacologic inhibition, βcatenin associates with the nucleoskeleton, defined as the insoluble nuclear fraction that provides structure to the integrated nuclear envelope, nuclear lamina and chromatin. Co-depleting LINC elements Sun-1 and Sun-2 interfered with both nucleoskeletal association and nuclear entry of βcatenin, resulting in decreased nuclear βcatenin levels. Our findings reveal that the insoluble structural nucleoskeleton actively participates in βcatenin dynamics. As the cytoskeleton transmits applied mechanical force to the nuclear surface to influence the nucleoskeleton and its LINC mediated interaction, our results suggest a pathway by which LINC mediated connectivity may play a role in signaling pathways that depend on nuclear access of βcatenin.